2018
DOI: 10.5152/turkjorthod.2018.17055
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Bleaching Treatments and Thermal-Mechanical Cycling on the Shear Bond Strength of Orthodontic Brackets

Abstract: Turkish Journal of Orthodontics (Turk J Orthod) is an international, scientific, open access periodical published in accordance with independent, unbiased, and double-blinded peer-review principles. The journal is the official publication of Turkish Orthodontic Society and it is published quarterly on March, June, September and December. Turkish Journal of Orthodontics publishes clinical and experimental studies on on all aspects of orthodontics including craniofacial development and growth, reviews on current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Nesta revisão sistemática, 5 autores decidiram recriar o ambiente da cavidade oral imergindo as amostras em saliva artificial, submetendo-as a estresse termomecânico ou inserindo-as em uma incubadora [12,[14][15][16]18].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nesta revisão sistemática, 5 autores decidiram recriar o ambiente da cavidade oral imergindo as amostras em saliva artificial, submetendo-as a estresse termomecânico ou inserindo-as em uma incubadora [12,[14][15][16]18].…”
Section: Resultsunclassified
“…O uso de certos agentes (caseína fosfopeptídeo de cálcio amorfo, ascorbato de sódio, extrato de casca de mangostão, quercetina, vitamina C, chá verde e camomila) Em relação aos agentes adesivos e ao protocolo que os autores utilizaram foi avaliada uma heterogeneidade, pois apenas 6 autores utilizaram o mesmo sistema, portanto não é possível excluir se esse fator pode afetar o valor de resistência ao cisalhamento (RCS) [11,[14][15][16][17]19].…”
Section: Resultsunclassified
“…Another limitation was that this study only investigated the SBS at 24 h and did not examine the long-term SBS. However, Carlos et al demonstrated that the shear bond strength after bleaching was not affected by the artificial aging of the materials using thermocycling [48]. Lastly, the long-term stability of the 35% 3-O-ethyl-l-ascorbic acid reagent should be evaluated before it can be used as a ready-to-use product.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment was composite resin material bonded on the teeth. Previous studies have reported that bleaching treatment could reduce the shear bonding strength (SBS) of brackets (Carlos et al, 2018;Sadeghian et al, 2021). However, there are few studies on the change of SBS of composite resin attachment under the condition of clear aligner treatment.…”
Section: Introductionmentioning
confidence: 99%